أقسام الالتفات وأغراضہ البلاغیة فی ضوء امثلۃ قرآنیۃ: THE TYPES OF DIGRESSION OR REFERENCE SWITCHING AND THEIR OBJECTIVE IN THE LIGHT OF QURANIC INSTANCES (Zia e Tahqeeq, 2025)
The present research aims at making out the term Al-Iltifat (digression or reference switching) found in the Holy Quran and coming out with a general scheme and purpose of Iltifat employed in the Holy Book. This study provides an account of the meaning of Iltifat from the Arab rhetoricians and subsequently the status of Iltifat as one of the rhetorical tropes. It has explored different aspects of Iltifat and its related features and highlighted new signification of Iltifat. An attempt has been made to introduce a new approach in looking at the Iltifat phenomenon by quoting some Quranic verses to demonstrate the application of this term from a new perspective. In the quoted verses a large number of instances of Iltifat have been traced, from which their general patterns are explained together with their significations. In the end, a summary of the important points is provided to point out that consideration of an instance of Iltifat in relation to other instances either in the particular verses where they occur or in the Quran as a whole, gives a more meaningful picture of its significance than that which comes out of the consideration of a solitary example within the confines of its immediate context. This research has shown that there is an extensive and complex use of this unique rhetoric style, Iltifat in the holy Quran. The instances of Iltifat in the Quran when construed provide a base for an overall understanding of each verse. It seems to have evolved a particular theme or function that is the essence of the Quran. It also shows that the occurrence of Iltifat in the Quran follows certain patterns that are related to the intended significations at the various locations where they appear in the Holy Quran. The findings of this study will hopefully pave the way for more investigations into rhetorical style in the holy Quran in general and Iltifat in particular.